Relationship Between Strength and Elasticity Modulus of Self-Consolidating Concrete Containing Different Types and Dosages of Pozzuolana - Turk, Kazim; Karatas, Mehmet; Turgut, Paki; Benli, Ahmet (Pamukkale Univ, 2010)
In this study, relationship between strength (compressive strength, tensile strength) and elastic modulus of self-consolidating concrete (SCC) that included different types and dosages of mineral admixtures (fly ash (FA) and silica fume (SF)) as replacement of Portland cement was investigated. In order to evaluate the workability of the mixtures, slump-flow, t(500), L-box and sieve segregation tests were carried out. In the following day of casting, the specimens were de-moulded and located in 20 +/- 2 degrees C water and cured for 28 days. Compressive strength, splitting tensile strength and elastic modulus tests were performed using a total of 3 specimens for each concrete property. Compressive strength-tensile strength and compressive strength-elastic modulus formulas obtained from regression analysis using a numerous data were compared with the equations obtained in the previous studies. Consequently, it was found that compressive strength-tensile strength and compressive strength-elastic modulus formulas obtained from this study can be used correctly to estimate the tensile strength and the elastic modulus of self-consolidating concrete.
Keywords: Self-consolidating concrete; Compressive strength; Tensile strength; Elasticity modulus